2003
DOI: 10.1046/j.1442-2042.2003.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire survey of Japanese urologists concerning the diagnosis and treatment of chronic prostatitis and chronic pelvic pain syndrome

Abstract: Objectives : We performed a questionnaire survey to investigate various issues in the diagnosis and treatment of chronic prostatitis/chronic pelvic pain syndrome by Japanese urologists and to clarify the circumstances surrounding prostatitis in Japan. Methods : Japanese urologists ( n = 1869) were surveyed by mail using a 17-item questionnaire to determine current diagnostic and treatment practices for prostatitis/chronic pelvic pain syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
2
21
1
Order By: Relevance
“…Nickel (1997) recommended a simpler and less expensive screening technique, namely the two-glass test (VB2 and VB3 or VB2 and EPS) be used to classify patients with CP. In Japan, although most urologists did not perform the four-glass test, they did perform the two-glass test (78.1%) to diagnose CP/CPPS (Kiyota et al, 2003). Thus, this result demonstrates that the two-glass test suits the circumstances in Japan.…”
Section: Gps General Practitioners; Pcps Primary Care Practitionersmentioning
confidence: 53%
See 4 more Smart Citations
“…Nickel (1997) recommended a simpler and less expensive screening technique, namely the two-glass test (VB2 and VB3 or VB2 and EPS) be used to classify patients with CP. In Japan, although most urologists did not perform the four-glass test, they did perform the two-glass test (78.1%) to diagnose CP/CPPS (Kiyota et al, 2003). Thus, this result demonstrates that the two-glass test suits the circumstances in Japan.…”
Section: Gps General Practitioners; Pcps Primary Care Practitionersmentioning
confidence: 53%
“…Much like the Canadian PCPs and urologists, 55.6% of Korean urologists did not believe that EPS cultures or other localising tests helped differentiate or diagnose the various types of CP (Ku et al, 2005a). A survey of Japanese urologists indicated that the four-glass test was not routinely carried out mainly because urologists believed that the procedures involved were too complicated (Kiyota et al, 2003). In fact, potential reasons for not performing the Fifty per cent of the urologists perform semen cultures, 51% also perform a prostate massage with cultures according to Meares and Stamey.…”
Section: Diagnosismentioning
confidence: 93%
See 3 more Smart Citations